Trust Development in International Joint Ventures, A case study of Finnish Indian Joint Venture - Ali, Tahir (My University, 2008)
Most scholars agree that the importance of trust in IJV relationships is a key concern for partner’s success in the intensely competitive and increasingly international modern business environment. This study examines the stage-wise development of trust and presents a model of stage-wise development of trust in IJV life cycle by using single case study. In theoretical part of the study, firstly the nature of IJVs is studied by identifying different stages of IJV life cycle and underlying motives for IJV formation. Secondly, the characteristics of trust has been discussed by shedding light on complexity of the concept trust, trustor and trustee characteristics, levels of trust and, dimensions of trust. Thirdly, the stage-wise development of trust has been discussed and relationship characteristics have been identified to discover their effect on development of trust. For the empirical study, the annual reports of the firm, company publications and, semi-structured face to face interview were used. The main conclusions are the following: trust starts with egoistic self interest motives called calculative based trust and then moves on towards more robust form of identification based trust. Before the IJV actually starts operating, calculative, competence, goodwill and contractual based trust dominate the partner search, selection and contractual agreement stages of IJV. Then knowledge based trust is produced when IJV starts operating. If every thing goes fine up to partner’s expectations and when partners further invest in IJV, then good will trust is strengthened. At the end identification based trust is produced and opposed to IJV, partners take joint steps in future new ventures. Furthermore, findings revealed fourteen relationship characteristics that underlie the dimensions of trust and push the trust from one dimension to other dimension. Findings also reveal that trust is not always incremental; it may decrease and then may be restored in its development process.
Keywords: International joint venture; Stages of international joint venture; Dimensions of trust; Stage-wise development of trust; Relationship characteristics.